Adventures in Zambezia [videorecording (DVD)] - Thornley, Wayne; Cook, Andrew; Silverston, Anthony; Forrest, Stuart (Film producer); Buckland, Mike; Suarez, Jeremy, 1990-; Breslin, Abigail, 1996-; Nimoy, Leonard; Goldblum, Jeff, 1952-; Jackson, Samuel L. (Sony Pictures Home Entertainment, 2013)
An adventurous young falcon named Kai leaves his remote country home for Zambezia, the fabulous city of birds, against his father's wishes. When his father is captured by an evil lizard who plans to attack the city, Kai must learn the importance of teamwork to rescue his father and save his new friends.